Taxonomic reappraisal of Gelidium coarctatum (Gelidiales, Rhodophyta) and Gelidium lineare sp. nov. from the tropical western Atlantic. Issue 5 (1st September 2016) - Iha, Cíntia; O'Shaughnessy, Kathryn A.; Guimarães, Silvia M.P.B.; Oliveira, Mariana C.; Freshwater, D. Wilson
Abstract: Gelidium coarctatum Kützing was a poorly known species described from the coast of Brazil. The name was picked up by Ugadim and applied to a common species on the tropical Brazil coast. Analyses of partial rbc L sequences and morphological characters of the G. coarctatum holotype have shown that it is a synonym of Gelidium capense (Gmelin) P.C.Silva and that the name G. coarctatum had been misapplied to the common tropical species of Gelidium in Brazil. The latter was described as Gelidium lineare sp. nov ., a species characterized externally by determinate lateral branches giving axes a generally linear outline and internally by copious rhizines being concentrated in the outer medulla and inner cortex. This species was also found to be common along the Caribbean coast of Panama and may be widespread in the tropical western Atlantic and Caribbean Sea.